Tradition and Change in Aril, A Siamese Village in Kelantan - Ismail, Mohamed Yusoff (The Australian journal of anthropology, 1982)
The paper traces the history of a Siamese village in the West Malaysia and outlines the manner in which its inhabitants have adopted to existence in a culturally Malay area. It documents the importance of the Buddhist religion for the maintenance of Siamese ethnic identity, a symbiosis with Chinese, and a generally harmonious, although subordinate relationship with local Malays.